Interline power flow controller (IPFC) characterization in power systems - A. Hussein, Nabil; A. Eisa, Ayamn; M. Mahmoud, Hassan; A. Shehata, Safy; A. Othman, El-Saeed (International Journal of Engineering and Technology, 2018)
Flexible AC Transmission Systems (FACTS) have been proposed in the late 1980s to meet and provide the electrical power system requirements. FACTS are used to control the power flow and to improve the power system stability. Interline power flow controller (IPFC) is a versatile device in the FACTS family of controllers and one of its latest generations which has the ability to simultaneously control the power flow in two or multiple transmission lines. This paper is tackling the IPFC performance in power systems; it aims to discuss the availability to define a known scenario for the IPFC performance in different systems. An introduction supported with brief review on IPFC, IPFC principle of operation and IPFC mathematical model are also introduced. IEEE 14-bus and 30-bus systems have chosen as a test power systems to support the behavior study of power system equipped with IPFC device. Three different locations have chosen to give variety of system configurations to give effective performance analysis.Â Â